Retinal microvascular changes in diabetic patients with diabetic nephropathy - Yujie Yan; Liping Yu; Chuan Sun; Haipeng Zhao; Hongsong Zhang; Zhijun Wang (BMC Endocrine Disorders, 2023)
Abstract Background To explore the characteristics of retina microvascular changes in patients with diabetic nephropathy (DN) and its risk factors. Methods Retrospective, observational study. 145 patients with type 2 diabetic mellitus (DM) and DN were included in the study. Demographic and clinical parameters were obtained from medical records. Presence of diabetic retinopathy (DR), hard exudates (HEs) and diabetic macular edema (DME) were evaluated according to the color fundus images, optical coherence tomography (OCT) and fluorescence angiography (FFA). Results DR accounted for 61.4% in type 2 DM patients with DN, of which proliferative diabetic retinopathy (PDR) accounted for 23.6% and sight threatening DR accounted for 35.7%. DR group had significantly higher levels of low-density lipoprotein cholesterol (LDL-C) (p = 0.004), HbA1c (P = 0.037), Urine albumin creatine ratio (ACR) (p < 0.001) and lower level of estimated glomerular filtration rate (eGFR) (P = 0.013). Logistic regression analysis showed DR was significantly associated with ACR stage (p = 0.011). Subjects with ACR stage3 had higher incidence of DR compared with subjects with ACR stage1 (OR = 24.15, 95%CI: 2.06–282.95). 138 eyes of 138 patients were analyzed for HEs and DME, of which 23.2% had HEs in posterior pole and 9.4% had DME. Visual acuity was worse in HEs group than in non-HEs group. There was significant difference in the LDL-C cholesterol level, total cholesterol (CHOL) level and ACR between HEs group and non-HEs group. Conclusions A relatively higher prevalence of DR was found in type 2 DM patients with DN. ACR stage could be recognized as a risk factor for DR in DN patients. Patients with DN needs ophthalmic examination more timely and more frequently.